Employee Ecological Behavior Through Green Transformational Leadership: The Mediating Role of Green Hrm Practices and Green Organizational Climate: A Systematich Literature Review - Dhea Agusty Ningrum; Teguh Satya Wira; Tomy Sun Siagian; Taufiq Hidayah; Jufrizen Jufrizen; Siti Mujiatun (CV Edujavare Publishing, 2026)
Increasing awareness of sustainability issues encourages organizations to integrate management practices oriented towards environmental conservation. This article aims to analyze the relationship between Green Transformational Leadership, Green Human Resource Management (GHRM), Green Organizational Climate (GOC), and Employee Ecological Behavior (EEB) through a literature review of previous studies. The method used is a literature review by analyzing reputable international scientific articles that discuss green leadership, green HR practices, green organizational climate, and employee ecological behavior. The results of the study indicate that Green Transformational Leadership has a positive influence on increasing Employee Ecological Behavior, both directly and through the mediation of Green Human Resource Management and Green Organizational Climate. GHRM practices can increase employees' abilities, motivation, and opportunities to implement environmentally friendly behavior, while GOC creates a work environment that supports the internalization of sustainable values. The literature synthesis also shows that the successful implementation of ecological behavior does not only depend on the characteristics of the leader, but requires the support of an integrated organizational system.